2002
DOI: 10.1007/s10126-002-0018-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Gastroenteritis Caused by Vibrio carchariae in Cultured Marine Fish

Abstract: Serious mortality among the cultured grouper Epinephelus coioides, characterized by a swollen intestine containing yellow fluid (gastroenteritis), occurred in 1993 in Taiwan. A bacterium isolated from the intestinal fluid and head kidney of moribund groupers was identified as Vibrio carchariae. Since then, the same Vibrio species has also been isolated from moribund black sea bream Acanthopagrus schlegeli, yellowfin sea bream A. latus, Japanese sea bass Lateolabrax japonicus, and red drum Sciaenops ocellatus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(58 citation statements)
references
References 0 publications
2
53
0
3
Order By: Relevance
“…The LD50 value estimated in the injection trial was 6.4×10 5 CFU g −1 per body. Numerous V. harveyi strains have been reported to exhibit pathogenicity toward a wide range of marine vertebrates and invertebrates such as sharks 3,9,10) , groupers 16,38) , flounder 31) , salmon 39) , sea bass 24) , rock robster 6) , penaeid shrimps 2,25) , and abalone 18,20) . In most cases, the vibrio pathogens were reported to be V. carchariae.…”
Section: 4×10mentioning
confidence: 99%
See 2 more Smart Citations
“…The LD50 value estimated in the injection trial was 6.4×10 5 CFU g −1 per body. Numerous V. harveyi strains have been reported to exhibit pathogenicity toward a wide range of marine vertebrates and invertebrates such as sharks 3,9,10) , groupers 16,38) , flounder 31) , salmon 39) , sea bass 24) , rock robster 6) , penaeid shrimps 2,25) , and abalone 18,20) . In most cases, the vibrio pathogens were reported to be V. carchariae.…”
Section: 4×10mentioning
confidence: 99%
“…Then, the bacterium might increase its mass on the surface for up to 5 days since the bacterial mass has been beyond the lethal dose against the host animal. However, diseases caused by V. harveyi infections were gastroentelitis, vasculitis, and eye disease 3,16,31,38) . Invasion from the foot muscle of a cultured abalone, H. diversicolor, was also reported 20) .…”
Section: 4×10mentioning
confidence: 99%
See 1 more Smart Citation
“…Vibrio carchariae has been described as an etiologic agent for some fish in cultivations. 27 Pereira et al 28 reported that forty samples of mangrove oysters (Crassostrea rhizophorae) served raw in 15 restaurants in Rio de Janeiro were evaluated in order to investigate the presence of Vibrio spp. They found that Vibrio parahaemolyticus, Vibrio carchariae, Vibrio alginolyticus and Vibrio vulnificus were the main species (> 60 %) isolated from raw oysters.…”
Section: Resultsmentioning
confidence: 99%
“…It is probably best known as the epidemiological agent responsible for luminosis vibriosis in shrimp, a disease characterized by slow growth, loss of appetite, and high shrimp mortality. It has also been associated with diseases in abalone (Haliotis tuberculata), 61 cobia (Rachycentron canadum), 62 rock lobster (Jasus verreauxi), 63 grouper (Epinephelus coioides), 64 red drum (Scaienops ocellatus), 65 salmonids, 66 summer flounder (Paralichthys dentatus), 67 pearl oysters (Pinctada maxima), 68 and other species of fish and shellfish. Depending on the fish and shellfish species, V. harveyi can also cause a host of other symptoms ranging from hemorrhaging, necrotizing enteritis, and gastroenteritis, to high mortalities without overt symptoms.…”
Section: Vibrio Harveyimentioning
confidence: 99%